The politics of visioning and coalition building in Malaysia a futures studies approach - Azhari Karim (Penerbit Universiti Sains Malaysia, 2021)
The idea for the book come from the event, the 14th General Elections in the country on 9 May 2018 that saw changes in the structure, personalities and systems in a Government.